Co-gasification of municipal sewage sludge and cotton stalk enhanced by metal-enriched texture dyeing sludge additives for syngas production. (1st June 2023) - Yan, Jingchun; Yan, Yongbo; Lai, Junjie; Jia, Dongyan; Jiao, Yong; Zhao, Xingyu; Yang, Li
Graphical abstract: Highlights: Texture dyeing sludge additives were active catalysts for co-pyrolysis/gasification. Activation energy for co-pyrolysis significantly decreased with sludge additives. Sludge additives enhanced tar abatement and promoted syngas production. Fe-containing species in sludge additives dominated the co-gasification performance. Abstract: In this study, co-gasification characteristics of municipal sewage sludge (MSS) and cotton stalk (CS) for syngas production enhanced by using metal-rich texture dyeing sludge (TDS) pyrolysis residues as additives were investigated in a TGA and a fixed bed reactor. Kinetic analysis results showed that the addition of TDS residue prepared at 600 °C (TDS-600) resulted in the reduction of activation energy of MSS/CS co-pyrolysis to the maximum extent. The syngas yield greatly increased with the rising temperature and steam volume fraction ( f H 2 O ). However, the excessive steam at high temperature may lead to the decrease of syngas yield due to the gas expansion effect. The maximum syngas yield of 0.808 m 3 /kg could be obtained at an optimal gasification temperature of 850 °C and a f H 2 O of 20 %. In the co-gasification of MSS and CS, the syngas yield increased from 0.683 without TDS-600 to 0.903 kJ/mol with 20 % TDS-600 and the tar content decreased from 40.15 % to 26.45 %, suggesting the outstanding catalytic effect of TDS-600 on promoting syngas yield and tar decomposition. The possible ecological risk of heavy metals in ashes after co-gasification was evaluated by the potential ecological risk index ( RI ). The calculated RI values of all samples were <50, demonstrating the safe application of ashes in agriculture industry.